The Studies on the Physico-Chemical and Organoleptic Characteristics of Apricot (Prunus armeniaca L.) Produced in Rawalakot, Azad Jammu and Kashmir During Storage - Ishaq, Saira; Rathore, Habib Ahmed; Majeed, Saima; Awan, Siddique; Ali Shah, Syed Zulfiqar (Pakistan Journal of Nutrition, 2009)
A highly significant effect (p